Persia and the Afghan occupation 1722 1725 (Journal of the College of Basic Education, 2023)
Persia succumbed during that period of time under the Afghan occupationwith its political entity and making it the focus of ambitions of neighboring countries, and due to the lack of an academic study that dealt withI renewed the topic and it is very important to address it so that the reader can know what the country has gone through.of his troubled situation at that stage.Afghanistan is located in the southwest of the Asian continent, and it is a mountainous region inhabited by tribesIt was under Persian control throughout the sixteenth and seventeenth centuries.But the weakness of the Safavid state during the days of Shah Hussein (1694-1722)The Ghazi Ghazi Afghans, especially in the early seventeenth century, demanded their independence.Which prompted the Persian government to send a strong and mighty governor named (Karkin Khan).The latter tasted woe and woe, so they rose up against him under the leadership of their prince (Was), and declared their independence.from Persia, and it was their intention to march towards Isfahan and occupy it, but the death hastenedtheir prince.